2021
DOI: 10.1039/d0cc08076d
|View full text |Cite
|
Sign up to set email alerts
|

Self-sorting of porous Cu4L2L′2 metal–organic cages composed of isomerisable ligands

Abstract: We report the self-sorting of a dynamic combinatorial library (DCL) of metal-organic cages composed of a rotationally isomerisable ligand. Convergence of the DCL occurs upon crystallisation and leads to low-symmetry...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…25a ). 143 The authors found that differing the solvent compositions used for crystallizing the metallo-supramolecular assemblies allowed to select distinct solid state morphologies, differing in their composition of ligand isomers and including pseudo-heteroleptic species, where two different ligand isomers are present in the same species ( Fig. 25b ).…”
Section: (Multi)functional Heteroleptic Cagesmentioning
confidence: 99%
“…25a ). 143 The authors found that differing the solvent compositions used for crystallizing the metallo-supramolecular assemblies allowed to select distinct solid state morphologies, differing in their composition of ligand isomers and including pseudo-heteroleptic species, where two different ligand isomers are present in the same species ( Fig. 25b ).…”
Section: (Multi)functional Heteroleptic Cagesmentioning
confidence: 99%
“…[27] However,t he design of crystalline cage materials with defined pore systems following basic geometrical principles is still highly challenging. [9,28] Since the lattice energy is rarely dominated by as ingle directional intermolecular motif,e ven subtle structural modifications at the molecular modules,e .g., inversion of chiral elements, [22g] frequently alter crystal packing,thus preventing isostructural crystallization even for structurally very similar cages. [17b,29] So far, isoreticular series of porous organic cage crystals have only been achieved with the help of additional design strategies such as computational crystal structure prediction, [30] chiral recognition [31] or structure-directing guests.…”
Section: Introductionmentioning
confidence: 99%
“…[27] However, the design of crystalline cage materials with defined pore systems following basic geometrical principles is still highly challenging. [ 9 , 28 ] Since the lattice energy is rarely dominated by a single directional intermolecular motif, even subtle structural modifications at the molecular modules, e.g., inversion of chiral elements, [22g] frequently alter crystal packing, thus preventing isostructural crystallization even for structurally very similar cages. [ 17b , 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…To assess the efficacy of the MOC cross-linking, we digested a sample of 3 using a protocol based on Ethylene glycol-bis(2-aminoethylether)-N,N,N′,N′-tetraacetic acid (EGTA). This digestion method results in metal-ligand dissociation without perturbing imine bonds ( Markwell-Heys et al, 2021 ). 1D and 2D H NMR analysis of the digested sample revealed the presence of unreacted L 2 , a mono-imine linked adduct, and a di-imine linked adduct in a ratio of 6:1:3, respectively ( Figures 4A, D ; Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%